Studi Tafsir Maudhu’i tentang Konsep dan Tata Cara Birrul Walidain - Sofi Sofiya; Dadan Rusmana (Gunung Djati Conference Series, 2022)
The purpose of this study is to discuss the concept of doing good to parents in the Qur'an. This study uses a qualitative method by using a maudhu'i interpretation study approach promoted by Abdul Hay al-Farmawi. The results and discussion of birrul walidain's research is a commendable character by being devoted to both parents then the word birrul walidain is mentioned in the Qur'an 13 times and from these verses it gives birth to a concept or procedure to be devoted to both parents, in Among them is always obeying the words and orders of parents if it is a virtue. This study recommends that research be carried out on other procedures for doing good in the Qur'an, such as procedures for doing good to teachers, relatives and others.